Japanese work culture from Hofstede's perspective: An analysis of workers' experiences through social media channels - Sari, Indah Puspita (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Japanese office workers are widely recognized for their discipline, innovation, and strong work ethic. These values reflect Japan’s collective dedication to organizational and national advancement. However, this cultural rigor also creates psychological pressure and limited individual freedom. Understanding this phenomenon through Hofstede’s cultural dimensions offers insights into Japan’s distinctive work behavior. Methods: This study employed documentation and literature study techniques. Video interviews of six Japanese workers from the Takashi From Japan YouTube channel were analyzed using Hofstede’s four cultural dimensions: power distance, collectivism vs. individualism, uncertainty avoidance, and masculinity/femininity. Supporting literature was reviewed to validate findings. Finding: Results reveal a high power distance, with workers showing strong obedience toward superiors and organizational hierarchy. Japanese work culture is predominantly collectivist, emphasizing group harmony and social contribution over personal interest. A high level of uncertainty avoidance leads workers to remain in rigid systems to minimize risk. Although less explored, masculinity is evident through hard work, self-sacrifice, and achievement orientation. Overall, the culture fosters stability and loyalty but often causes psychological strain and reduced personal expression. Conclusion: Japanese work culture is characterized by hierarchy, collectivism, and avoidance of uncertainty, reinforcing discipline and organizational stability while creating pressure and emotional fatigue among workers. Novelty/Originality of this article: This study offers a unique qualitative exploration of Japanese work culture through Hofstede’s framework based on real worker experiences from digital media sources, providing fresh insights into cultural dynamics in modern Japan.